Esthetic dentistry in clinical practice - Geissberger, Marc (Ames, Iowa : Wiley-Blackwell, 2010)
'As esthetic dentistry continues to grow in popularity, dentists are offered an opportunity to expand their practices and attract new patients. Esthetic Dentistry in Clinical Practice provides dentists with the skills to take advantage of that opportunity. Clearly outlining esthetic procedures, the book enables dentists to treat patients in an efficient and clinically sound manner, bringing esthetic dentistry to everyday practice'--Provided by publisher
Chapter 11: Direct Composite Restorative Techniques -- Brian J. Kenyon DMD, BA -- Kenneth G. Louie DDS, BS -- Bina Surti DDS -- Chapter 12 - Selecting Indirect Restorative Materials -- Jeffrey Miles DDS -- Karen A. Schulze DDS, PhD -- Daniel Castagna DDS -- Chapter 13 - Color and Shade Selection -- James Milani DDS, BS -- Laura Reid DDS, BS -- Richard White DDS, BS -- Chapter 14 - Preparation Design for Indirect Restorations in Esthetic Dentistry -- Foroud Hakim DDS, MBA, BS -- Jessie Vallee DDS -- Marina Wasche DDS, BS -- Chapter 15 - Soft Tissue Management, Impression Materials and Techniques -- Gitta Radjaeipour DDS, BS -- Bina Surti DDS, BS -- Marc Geissberger DDS, MA, BS -- Chapter 16 - Provisional Restorations -- Jeffrey P. Miles DDS -- Dudley Cheu DDS, MBA -- Daniel Castagna DDS -- Chapter 17 - Laboratory Fabrication of Esthetic Restorations -- Jeffrey P Miles DDS -- Karen A. Schulze DDS, PhD -- Daniel Castagna DDS -- Chapter 18 - Luting Agents for Dental Restorations -- Karen A. Schulze DDS, PhD -- Richard G. Lubman DDS -- Chapter 19 - Restoration Delivery -- Marc Geissberger DDS, MA, BS -- Chapter 20 - Protective Occlusal Splints -- Laura Reid DDS, BS -- Richard White DDS, BS
Keywords: Dentistry -- Aesthetic aspects; Esthetics, Dental